Grant-Making Criteria for Developing Useful and Usable Marine Science: A Philanthropic Perspective - Landrum, Jason P.; Hudson, Charlotte G.; Close, Sarah L.; Knight, Emily; Paquin, Rachel-Marie; Bell, Victoria; Ripple, Kayla (Frontiers in Marine Science, 2022)
Decades of scholarship and practice highlight the need for scientific research that informs individuals on the front lines of decision-making. Funding organizations can play an important role in supporting useful and usable research by discussing the criteria and processes they use to guide the development and review of funded projects. However, practical examples of how funders can engage with grantees on the design of research efforts are not widely available. In this article, we respond to calls for more information in this area by presenting one example of evaluation criteria and guidance questions used by a philanthropic grant-making program that is focused on user-driven research. We describe this process through the lens of a funded research project that was designed to inform improvements in coastal habitat restoration. We hope that a closer look at an example of how to evaluate project ideas for their potential to provide critical information to decision-makers can be useful for other funders and researchers trying to produce useful and usable science.